Strategi Penetapan Harga Dalam Meningkatkan Kepuasan Jamaah Umrah Di PT. Ziarah Hati Indonesia Surabaya - Fahmi, M. Fahmi Ashari; Zen, Muhamad Zen; Fatmawati, Fatmawati (UIN Mataram, 2024)
Business development nowadays has grown so rapidly. Seeing these conditions, business people are required to have the right business strategy to fulfill sales. One of the business strategies that can be carried out is a pricing strategy. Pricing strategy is a method used to determine the best price for a service, which is expected to provide benefits for the company's sustainability. The aim of this research is to analyze pricing strategies and the factors that influence them at PT. Pilgrimage to the Heart of Indonesia Surabaya. This research uses a qualitative research method with a case study type at PT. Pilgrimage to the Heart of Indonesia Surabaya. Data collection techniques use observation, documents and interviews. The results of this research are that 1) in determining prices, PT. Ziarah Hati Indonesia Surabaya has several strategies implemented, including geographic pricing, discounts or discounts, promotional pricing and discriminatory pricing. 2) there are several internal and external factors that influence price setting at PT. Ziarah Hati Indonesia Surabaya, namely internal factors including (good service quality and company resources) and external factors (competition and government policy).